Leveraging connectivity to innovate for a differentiated customer experience : a study into the management of interaction between financial services organisations and their external environment to enhance the innovation process for the delivery of a differentiated customer experience - Ganzevoort, Boto Wybrand (Stellenbosch : Stellenbosch University, 2012)
Thesis (MComm)--Stellenbosch University, 2004.